What is integrative medicine? Establishing the decision criteria for an operational definition of integrative medicine for general practice health services research in Australia - Jennifer Hunter; Joanna E. Harnett; Wai-Jo Jocelin Chan; Marie Pirotta (Integrative Medicine Research)
Background: Operational definitions outline how a conceptual definition will be measured for consistent, reproducible data collection and analysis. This article reports the decision criteria that will be used for an operational definition of integrative medicine (IM) in a secondary analysis of an Australian national survey of general practitioner activity. Methods: A multidisciplinary team applied an iterative approach, informed by expert knowledge and literature reviews to establish decision criteria for categorizing the terms in the Australian clinical interface terminology of the International Classification of Primary Care, second edition (ICPC-2 PLUS) and the Coding Atlas for Pharmaceutical Substances, according to whether they reflected IM, conventional/mainstream medicine (MM), or both IM and MM (IM/MM). Results: The final decision criteria categorized all terms for examinations, investigations, advice/counselling, and drugs with synthetic ingredients, and terms for referrals to secondary care services and healthcare practitioners that are not a traditional or complementary medicine practitioner as MM. Terms that could apply to both styles of clinical practice (e.g., preventive health, lifestyle medicine, psychosocial and some drugs with natural ingredients) were categorised as IM/MM. The remaining terms, that mostly reflected the World Health Organization's theoretical definitions of traditional and complementary medicine, were categorized as IM. Conclusion: Differentiating between integrative and conventional/mainstream medicine in general practice is context specific and not always possible. The category IM/MM proposes integrative medicine as an extension, rather than an alternative. The rationale for the integrative medicine operational definition has relevance for researchers and health services in Australia, and internationally.